Distribuzione spazio-temporale dell’ittioplancton lungo un gradiente mare-laguna - Facca, Chiara; Cavraro, Francesco; Redolfi Bristol, Simone; Franzoi, Piero (Biologia Marina Mediterranea, 2025)
The study examined sea-lagoon connectivity in the Venice lagoon, analyzing the distribution of eggs and larvae of fish fauna between 2015 and 2020. Egg densities were higher in the sea, while larvae were more evenly distributed between the sea and the lagoon. Marine migratory species were found to be effective indicators of the correct functioning of sea-lagoon connectivity and of the nursery role played by lagoons for numerous species.